2023
DOI: 10.1177/14034948231184288
|View full text |Cite
|
Sign up to set email alerts
|

Weekly pattern of alcohol-attributable male mortality before and after imposing limits on hours of alcohol sale in Lithuania in 2018

Abstract: Aims: From 1 January 2018, the number of retail hours for the sale of alcohol was reduced from 14 to 5 hours on Sundays and from 14 to 10 hours on the other days of the week in Lithuania. The significant reduction of hours for the sale of alcohol on Sundays may have affected the distribution of alcohol-attributable deaths during the week. This study aimed to examine the change in the weekly pattern of alcohol-attributable male mortality before and after imposing limits on the hours when alcohol can be sold. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This has also been corroborated using a different direct methodology approach examining changes after major policy implementation. Stumbrys and colleagues [ 13 ] showed that the typical increases in CVD mortality on Mondays, which had been found in Lithuania and other post-Soviet countries…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has also been corroborated using a different direct methodology approach examining changes after major policy implementation. Stumbrys and colleagues [ 13 ] showed that the typical increases in CVD mortality on Mondays, which had been found in Lithuania and other post-Soviet countries…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Lithuania-specific RRs, and based on the current evidence, we argue that Russian RRs better describe the CVD burden in males, due to their high prevalence of episodic heavy drinking— especially important for ischemic disease [ 44 , 54 ] which has been linked to an overall irregular drinking pattern with many abstinent days but a high overall level of consumption [ 13 , 65 ]. We further base our argument on the direct results of earlier studies which have shown an impact from the implementation of major alcohol control policies (see examples in the last paragraph).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the policy of more significant reduction of alcohol sale hours was justified using past research arguments showing that alcohol could be associated with higher mortality burden during the weekends, this policy was widely criticized. The opposing interest groups described it as "ineffective" or "illogical"; however, the independent analysis led by Dr. Daumantas Stumbrys [1] demonstrated a positive effect of the alcohol control policy in reducing the alcohol-related mortality in men. After comparing mortality cases from external causes and cardiovascular disease it was demonstrated that the mortality has been reduced on Sundays (for external causes) and Mondays (for cardiovascular disease).…”
mentioning
confidence: 99%